Potensi Antioksidan Kombinasi Ekstrak Daun Cocor Bebek (Kalanchoe pinnata L.) Dan Ekstrak Daun Kratom (Mitragyna speciosa Korth.) Dengan Metode DPPH - Meisa, Devina; Rohama, Rohama; Rahmadani, Rahmadani; Nastiti, Kunti (Jurnal Pelayanan Kefarmasian dan Sains, 2025)
Background: Indonesia is a country that has plants that are widely used by the public as traditional medicine, including bebek cocor leaves (Kalanchoe pinnata L.) and kratom leaves (Mitragyna speciosa Korth.) which have been proven to contain antioxidants and are empirically proven to be a pain reliever. Objective: To determine the IC50 of the combined extract of cocor bebek leaves (Kalanchoe pinnata L.) and kratom leaves (Mitragyna speciosa Korth.). Methods: In this study, simplicia leaves of cocor bebek (Kalanchoe pinnata L.) and kratom leaves (Mitragyna speciosa Korth.) were extracted by maceration. Phytochemical screening and antioxidant activity tests were carried out on each extract. Antioxidant activity testing was carried out using the DDPH (2,2-diphenyl-1-picrylhydrazyl) method. Antioxidant activity was tested quantitatively using Uv-Vis spectrophotometry at a wavelength of 528 nm with the comparison standard used being Vitamin C. Results: The results show that the ethanol extract of Cocor Bebek leaves and Kratom leaves alone has very strong antioxidant activity with IC50 values ​​of 17,96 ppm and 14.43 ppm. The combination with a ratio of 2:1 obtained the lowest IC50 value, namely, 10.60 ppm compared to 1:1 with an IC50 of 15.14 ppm and 1:2 with an IC50 of 12.72 ppm Conclusion: The highest antioxidant activity is found in a combination of ethanol extract of Cocor Bebek leaves and Kratom leaves in a ratio of 2:1 with a lower IC50 than either alone.